Designing English Teaching Materials Containing Popular Culture - S. Sudiran; Dyah Estu Kurniawati; A. Adityo (Direktorat Penelitian dan Pengabdian Kepada Masyarakat, 2020)
There are two main objectives in conducting this research, namely: 1) describing how popular culture can be designed into English teaching materials; 2) explaining how to implement English teaching material containing popular culture in the classroom. This study uses qualitative methods using interviews and text or document analysis techniques as research instruments. The informants interviewed were postgraduate students of the English Language Education Department, University of Muhammadiyah Malang, Indonesia. They took the Material Development course. And the documents analyzed were learning devices such as syllabus and teaching plan that had been designed. The research data is in the form of interviews and texts related to popular culture such as pictures, music, food and drinks, sports and books. The results of the study show that popular culture such as images of food and drinks, music, sports and entertainment can be developed into English teaching materials. Informants implemented English teaching material that contained popular culture in the classroom through peer teaching programs.